Ballistic formation of high-intensity low-energy gas ion beams - Ryabchikov A. I. Aleksandr Ilyich; Sivin D. O. Denis Olegovich; Shevelev A. E. Aleksey Eduardovich; Akhmadeev Yu. Kh. Yury Khalyafovich; Korneva O. S. Olga Sergeevna; Ivanova A. I. Anna Ivanovna; Lopatin I. V. Iljya Vladimirovich (2020, 2020)
Title screen